2021
DOI: 10.35445/alishlah.v13i2.932
|View full text |Cite
|
Sign up to set email alerts
|

Online Learning Problems and the Principal’s Efforts to Overcome the Problems

Abstract: The spread of the Coronavirus (Covid-19) has brought various drastic changes to human life, one of which is the mode of learning that should be transformed into an online mode. However, the complexities of online learning leave some problems. Thus, this qualitative study aimed to investigate the online learning processes, problems, and the principal’s solutions at MA Muhammmadiyah Kampung Delima, Rejang Lebong, Bengkulu Province. The principal and five selected teachers were involved as the participants. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Even with smaller portion, that issue still becomes their difficulties during the implementation of online learning. The product of the present study is in line with the other study which mentioned that unstable network is one problem found in online learning (Asha, 2021).…”
Section: Obstacles In Teaching and Learning English During The Pandem...supporting
confidence: 90%
See 1 more Smart Citation
“…Even with smaller portion, that issue still becomes their difficulties during the implementation of online learning. The product of the present study is in line with the other study which mentioned that unstable network is one problem found in online learning (Asha, 2021).…”
Section: Obstacles In Teaching and Learning English During The Pandem...supporting
confidence: 90%
“…However, the finding of other study does not include psychological factors as problems found in online learning (Asha, 2021). This study focuses merely on casual components such as lack of facility, bad network, minimum communication between teachers and students, insufficient parental care, limitation of students' learning strategies and a large number of tasks by teachers or lecturers.…”
Section: Obstacles In Teaching and Learning English During The Pandem...mentioning
confidence: 95%
“…The teacher seldomly was late in uploading material in elearning. This was aligned with (Altakhaineh & Rahrouh, 2015;Asha, 2021;Brueck & Lenhart, 2015;Ismail et al, 2020). Even though, the problems and challenge existed, the deliverance of online learning in STKIP MNC was going smoothly.…”
Section: Figure 2 Upload Date Of Teachermentioning
confidence: 72%